Дослідження властивостей фосфорильованого сорбенту при вилученні іонів Cu(II) в присутності солей жорсткості - Хохотва, Олександр Петрович; Лиштва, Павло Валерійович (НТУ "ХПІ", 2018)
Отримано фосфоровмісний вуглецевий сорбент карбонізацією соснової тирси, просякнутої розчинами (NH₄)₃PO₄ або сумішшю (NH₄)₃PO₄ і карбаміду. Кінетика сорбції найкраще описується рівнянням псевдо-другого порядку. Ізотерми сорбції, отримані для фосфоровмісного сорбенту в Н⁺- і Na⁺-формах, а також необробленої соснової тирси, описуються рівнянням Ленгмюра. Сорбент у Na⁺-формі мав значення сорбційної ємності 20,6 мг/г – найвище серед досліджених сорбентів, найнижче – у необробленої тирси – 7,7 мг/г. Досліджено ефективність отриманих матеріалів при вилученні іонів міді з однокомпонентних розчинів та у присутності іонів кальцію.

Activated carbon has been used in water treatment technologies for many decades on a final stage of treatment process. It is well-known, however that activated carbon is an expensive material. Although any carbonaceous material with high carbon content and low ash is feasible for the production of activated carbon, in practice a limited number of carbon precursors exist as the principal sources, i.e. wood, coal and coconut shells. Agricultural by-products are potentially attractive feedstock because they are highly available and renewable raw materials and generated as low-cost byproducts. The research has been focused on the utilization of locally available biomass materials for the production of carbons with good adsorbing properties. Phosphorus-containing carbon sorbent was synthesized by carbonization of pine sawdust, soaked in 10% (NH₄)₃PO₄ solution or a mixture of (NH₄)₃PO₄ and carbamide. The effect of contact time on the efficiency of Cu(II) sorption by the obtained material from the model aqueous solutions was investigated. The equilibrium in the system sorbent-sorbate was reached in 1.5 hours, though half of the copper content was absorbed during the first 30 minutes. Experimental data were processed according to the pseudo-first pseudo-second-order kinetic models. Sorption of copper by phosphorylated carbon sorbent derived from pine sawdust from aqueous solutions was quite fast. Kinetics of the copper ions sorption was best described by pseudo-second order kinetic model. Sorption isotherms obtained for phosphorus-containing sorbent in H⁺- and Na⁺-forms, as well as the original untreated pine sawdust, had a maximum of sorption and can be well described by Langmuir equation. During the sorption process pH of solutions fell to 3,2-3,5. Sorbent in Na-form had maximum sorption capacity 20,6 mg/g – the highest value among the studied sorbents, the lowest one was in case of untreated sawdust – 7,7 mg/g. Efficiency of copper ions removal was investigated in the presence of Са²⁺.
Investigation of sorption properties of phosphorylated sorbent at the removal of Cu(II) ions in the presence of hardness salts
Keywords: соснова тирса; важкі метали; адсорбція; кінетика; ізотерми; pine sawdust; heavy metals; adsorption